2012
DOI: 10.1007/s10664-012-9233-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrating conceptual and logical couplings for change impact analysis in software

Abstract: The paper presents an approach that combines conceptual and evolutionary techniques to support change impact analysis in source code. Conceptual couplings capture the extent to which domain concepts and software artifacts are related to each other. This information is derived using Information Retrieval based analysis of textual software artifacts that are found in a single version of software (e.g., comments and identifiers in a single snapshot of source code). Evolutionary couplings capture the extent to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 79 publications
(94 reference statements)
1
66
0
13
Order By: Relevance
“…For example, the rule {A, B}→ C found in the sales data of a supermarket indicates that a customer who buys A and B together, is also likely to buy C (Oliva and Gerosa 2011). Two classes change at the same time when changes in one class A are made in response to a change in another class B. Kagdi et al (2013) state that logical coupling captures the extent to which software artefacts co-evolve and this information is derived by analysing patterns, relationships and relevant information of source code changes mined from multiple versions (of software systems) in software repositories (e.g., Subversion and Bugzilla). According to Lanza et al (D'Ambros et al 2006) it is useful to study logical coupling because it can reveal dependencies not revealed by analyzing the source code (Yu 2007) only.…”
Section: Logical Couplingmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the rule {A, B}→ C found in the sales data of a supermarket indicates that a customer who buys A and B together, is also likely to buy C (Oliva and Gerosa 2011). Two classes change at the same time when changes in one class A are made in response to a change in another class B. Kagdi et al (2013) state that logical coupling captures the extent to which software artefacts co-evolve and this information is derived by analysing patterns, relationships and relevant information of source code changes mined from multiple versions (of software systems) in software repositories (e.g., Subversion and Bugzilla). According to Lanza et al (D'Ambros et al 2006) it is useful to study logical coupling because it can reveal dependencies not revealed by analyzing the source code (Yu 2007) only.…”
Section: Logical Couplingmentioning
confidence: 99%
“…Identifiers used by developers for names of classes, methods, or attributes in source code or other artifacts contain important information and account for approximately half of the source code in software (Kagdi et al 2013). These names often serve as a starting point in many program comprehension tasks.…”
Section: Semantic Couplingmentioning
confidence: 99%
See 3 more Smart Citations